Comparative Study of the Changes in Climatic Condition and Seasonal Drought in North-Western Part of Bangladesh - Khan, Riaz Hossain; Islam, Mohammad Saiful (Journal of the Asiatic Society of Bangladesh, Science, 2018)
The study examines the long-term and seasonal climatic variations in north-western part of Bangladesh (NWPB). Long-term variation of different climatic parameters reveals that significant increases in temperature are associated with decreasing evaporation which could be attributed to wind speed variation and seasonal variation of temperature. Increase of monsoon rainfall during monsoon period and scarcity or absence of rainfall during dry periods increase the region’s vulnerability to monsoon flood and seasonal drought, respectively. The area witnesses a single peak of rainfall in July during the first half of the study period (1964-1985), whereas the same experiences bimodal peak of rainfall during July and September in the second half of the study period (1986-2007). This may signify the changes of climatic condition in the studied area. Annual variability of rainfall as well as the unpredictable shifting of rainfall periods might be a possible reason for the seasonal drought. The aridity index indicates that the overall dryness of the area has increased during winter season. The study shows that humidity increases at all stations throughout the year. The study also shows that long-term seasonal variation of both surface and groundwater level is also prominent. Gradual decrease of surface water level was observed in Teesta River which might be due to unilateral withdrawal of surface water in the upper riparian. Detailed investigation on hydrometeorology of the study area is required to see whether there is any trend of climate change in the area. Asiat. Soc. Bangladesh, Sci. 44(2): 195-210 December 2018